Understanding the phase behavior from multiple-step isothermally crystallized poly(3-hexylthiophene)s. (19th August 2016) - Peng, Ying; He, Zhiqun; Li, Han; Liang, Chunjun
Abstract: In this work, multiple transitions from isothermally crystallized poly(3-hexylthiophene) (P3HT) and their correlations to the structure were investigated. It was discovered that high and low temperature crystallites of varying degree orders can be formed in P3HT matrices during the isothermal crystallization. The high temperature crystallite was highly ordered crystalline form having melting temperature around 230 °C; while the low temperature crystallite was quasicrystalline of limited ordered having a varying endothermic transition temperature depending on crystallization conditions. The population of high temperature crystallites can be manipulated by the variation of isothermal crystallization conditions. The small angle X-ray scattering revealed a progressive phase separation at appropriate crystallization temperature and/or prolonged crystallization times. Graphical abstract: Highlights: High and low temperature crystallites of same crystalline forms can be developed in P3HT. High temperature crystallite is highly ordered melting at relative high-temperature. Low temperature crystallite has a low degree order melting at a variable and lower temperature. Isothermal crystallization can increase the high temperature crystallite population. Enhanced temperature and/or prolonged crystallization time promoted phase separation.